Stereotactic body radiotherapy improves the survival of patients with oligometastatic non‐small cell lung cancer - Ouyang, Wen (Cancer Med, 2019)
PURPOSE: The aim of the study was to evaluate the efficacy and safety of stereotactic body radiotherapy (SBRT) for pulmonary lesions in oligometastatic non‐small cell lung cancer (NSCLC) patients, to explore prognostic factors of progression‐free survival (PFS) and overall survival (OS), to validate improved survival contributed by SBRT in oligometastatic NSCLC patients. PATIENTS AND METHODS: A total of 71 oligometastatic NSCLC patients with 86 pulmonary lesions treated with SBRT in our institute between 2012 and 2018 were included. Local control (LC), progression‐free survival (PFS), and overall survival (OS) were calculated using Kaplan‐Meier method. Prognostic factors of PFS and OS were analyzed using univariate and multivariate Cox analyses. Subgroup analyses were performed to investigate the impact of SBRT on PFS and OS during first line systemic treatment. RESULTS: After a median follow‐up of 17.6 months, 2‐year LC and OS rates were 82.6% and 55.3%, respectively. No grade 4 or more toxicities were observed. Multivariate analysis showed systemic treatment regimen before SBRT was an independent prognostic factor of PFS, but not for OS. Among this cohort, patients receiving first line target therapy could show a better PFS and OS than those undergoing first line chemotherapy (target therapy vs chemotherapy, PFS, 26.4 m vs 6.9 m; OS, 34.8 m vs 15.5 m). CONCLUSIONS: SBRT for pulmonary lesions was a feasible and tolerable option for oligometastatic NSCLC patients. Delivery of SBRT for pulmonary lesions improved outcomes of oligometastatic NSCLC patients. Finally, SBRT combined with first line target therapy might have optimal outcomes.